2004
DOI: 10.1111/j.1529-8817.2004.04060.x
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF A PSYCHROPHILIC GREEN ALGA FROM LAKE BONNEY ANTARCTICA: CHLAMYDOMONAS RAUDENSIS ETTL. (UWO 241) CHLOROPHYCEAE1

Abstract: An unusual psychrophilic green alga was isolated from the deepest portion of the photic zone (o0.1% of incident PAR) at a depth of 17 m in the permanently ice-covered lake, Lake Bonney, Antarctica. Here we identify and report the first detailed morphological and molecular examination of this Antarctic green alga, which we refer to as strain UWO 241. To determine the taxonomic identity, UWO 241 was examined using LM and TEM and partial sequences of the small subunit (SSU), internal transcribed spacer (ITS) 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 43 publications
4
74
3
1
Order By: Relevance
“…Among the Chlamydomonas samples, however, noticeable differences in the FA composition could be observed. While the three tested strains of Chlamydomonas are almost indistinguishable in terms of their phylogeny [73], they originate from very different ecosystems. The Antarctic strain CCMP 1619 was the only one to accumulate the -3 PUFA linolenic acid (18:3) at a high concentration (12% of the total FA composition).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the Chlamydomonas samples, however, noticeable differences in the FA composition could be observed. While the three tested strains of Chlamydomonas are almost indistinguishable in terms of their phylogeny [73], they originate from very different ecosystems. The Antarctic strain CCMP 1619 was the only one to accumulate the -3 PUFA linolenic acid (18:3) at a high concentration (12% of the total FA composition).…”
Section: Discussionmentioning
confidence: 97%
“…A hypothetical explanation which has not been evaluated in our study, for the overall strong NF-B inhibitory activity of the tested microalgal extracts, could be an ubiquitously high concentration of NF-B-inhibiting carotenoids. High concentrations of carotenoids, and of astaxanthin in particular, have been previously reported in Chlamydomonas, Chlorococcum, and other microalgae [50,73,81], and most carotenoids are potent antioxidants [30] [82], which renders them capable of interfering with NF-B activation [83].…”
Section: Discussionmentioning
confidence: 99%
“…These latter pigments are primarily photoprotective and increase lutein's nonphotochemical quenching ability (Demmig-Adams et al 1999). Lutein was present at higher concentrations than in the shade-adapted sub-ice alga Chlamydomonas raudensis UWO 241 grown at 20 µmol photons m -2 s -1 and 8°C (282 ± 5.2 mmol mol -1 chl a) (Pocock et al 2004), but was comparable to the mesophile C. reinhardtii grown at 150 µmol photons m -2 s -1 and 16°C (747 ± 105 mmol mol -1 chl a) (Morgan et al 1998 Chlamydomonas sp. ARC has an 18S rRNA sequence that is only slightly different from 5 other strains that form a clade of 6 closely related psychrophiles, which we have dubbed the 'polar clade', including the Antarctic marine strains Chlamydomonas sp.…”
Section: Discussionmentioning
confidence: 98%
“…In any case, psychrophily seems to be a rather transient trait among some chlorophytes (Hoham et al 2002). There is at least one other example of a psychrophilic and mesophilic strain of the same species, namely C. raudensis Ettl (UWO 241) isolated from an ice-covered saline lake in Antarctica (Pocock et al 2004, Szyszka et al 2007). Thus, we hypothesize that this seemingly psychrophilic clade of Chlamydomonas simply exhibits a great amount of flexibility with respect to adaptation to a wide range of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Harris (2009) reported that the usual laboratory species of Chlamydomonas grow well in the range of 20-25°C. Pocock et al (2004) used 29°C as optimum temperature for the culture of Chlamydomonas noctigama in Bold's basal medium. The result varies might be due to the change in medium.…”
Section: Phmentioning
confidence: 99%